Step-by-step explanation:
i think 48888 because i think so and you do to
1/64 & 16
hope that helped :)
Answer:
10 ÷ 0.2=50
Step-by-step explanation:
10 lbs in total. Each batch uses 0.2 lbs.
We can find how many batches can be made by dividing 10 by 0.2.
10 ÷ 0.2=50
Juan is incorrect because if they could only make 5 batches then they would have only had 1 pound of red dye available.
They have 10 pounds of red dye available to make marbles, and if each batch takes only 0.2 lbs of it, then they can make 50 batches of marbles.
Answer:
x • (x^3 - 3x^2y + 3xy^2 + 7y^3)
Step-by-step explanation:
(8x • (y^3)) + x • (x - y)^3
2^3xy^3 + x • (x - y)^3
Evaluate : (x-y)^3 = x^3-3x^2y+3xy^2-y^3
Pull out like factors :
x^4 - 3x^3y + 3x^2y^2 + 7xy^3 =
x • (x^3 - 3x^2y + 3xy^2 + 7y^3)
x^3 - 3x^2y + 3xy^2 + 7y^3 is not a perfect cube
Simplify <span><span><span>12</span>x</span><span><span>12</span>x</span></span> to <span><span>x2</span><span>x2</span></span>
<span><span><span>x2</span>−<span>34</span>y=−2</span><span><span>x2</span>−<span>34</span>y=−2</span></span>
2 Simplify <span><span><span>34</span>y</span><span><span>34</span>y</span></span> to <span><span><span>3y</span>4</span><span><span>3y</span>4</span></span>
<span><span><span>x2</span>−<span><span>3y</span>4</span>=−2</span><span><span>x2</span>−<span><span>3y</span>4</span>=−2</span></span>
3 Subtract <span><span>x2</span><span>x2</span></span> from both sides
<span><span>−<span><span>3y</span>4</span>=−2−<span>x2</span></span><span>−<span><span>3y</span>4</span>=−2−<span>x2</span></span></span>
4 Multiply both sides by <span>44</span>
<span><span>−3y=(−2−<span>x2</span>)×4</span><span>−3y=(−2−<span>x2</span>)×4</span></span>
5 Regroup terms
<span><span>−3y=4(−2−<span>x2</span>)</span><span>−3y=4(−2−<span>x2</span>)</span></span>
6 Divide both sides by <span><span>−3</span><span>−3</span></span>
<span><span>y=<span><span>4(−2−<span>x2</span>)</span><span>−3</span></span></span><span>y=<span><span>4(−2−<span>x2</span>)</span><span>−3</span></span></span></span>
7 Simplify <span><span><span>4(−2−<span>x2</span>)</span><span>−3</span></span><span><span>4(−2−<span>x2</span>)</span><span>−3</span></span></span> to <span><span>−<span><span>4(−2−<span>x2</span>)</span>3</span></span><span>−<span><span>4(−2−<span>x2</span>)</span>3</span></span></span>
<span><span>y=−<span><span>4(−2−<span>x2</span>)</span>3</span></span></span>